2010
DOI: 10.1007/s00415-010-5836-5
|View full text |Cite
|
Sign up to set email alerts
|

The role of cytokines in Guillain–Barré syndrome

Abstract: Cytokines play an important role in the pathogenesis of autoimmune diseases including Guillain-Barré syndrome (GBS) and its animal model experimental autoimmune neuritis (EAN). In this article, we reviewed the current knowledge of the role of cytokines such as TNF-α, IFN-γ, IL-1β, IL-6, IL-12, IL-18, IL-23, IL-17, IL-10, IL-4 and chemokines in GBS and EAN as unraveled by studies both in the clinic and the laboratory. However, these studies occasionally yield conflicting results, highlighting the complex role t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
77
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 177 publications
(157 reference statements)
0
77
0
3
Order By: Relevance
“…[121314] Besides, the pro-inflammatory role of IL-6 in experimental autoimmune neuritis and GBS, it is shown that it may have additional neuroprotective effects by reducing TNF, IL-1, and promoting SC proliferation and remyelination. [15] IL-8 along with IL-1ra (receptor alpha) mediates the recruitment and activation of lymphocytes and monocytes expressed in the CSF of GBS patients. [12] Both IL-6 and IL-8 along with other cytokines released by tubular epithelia in response to reduced total or regional blood flow to the kidney enhances inflammation and cell injury.…”
Section: Discussionmentioning
confidence: 99%
“…[121314] Besides, the pro-inflammatory role of IL-6 in experimental autoimmune neuritis and GBS, it is shown that it may have additional neuroprotective effects by reducing TNF, IL-1, and promoting SC proliferation and remyelination. [15] IL-8 along with IL-1ra (receptor alpha) mediates the recruitment and activation of lymphocytes and monocytes expressed in the CSF of GBS patients. [12] Both IL-6 and IL-8 along with other cytokines released by tubular epithelia in response to reduced total or regional blood flow to the kidney enhances inflammation and cell injury.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, IL-6 in the presence of transforming growth factor (TGF)- β 1, and IL-6, IL-23 in combination with IL-1 β had been proved to be the effective factors responsible for the differentiation of Th17 cells and the production of IL-17; these cytokine milieux may also facilitate the expression of IL-22 [26, 27]. IL-6, IL-1 β , IL-23, and TNF- α are all proinflammatory cytokines and have an important role in the pathogenesis of GBS [28]. Therefore, it is safe to conclude in our study that the extensive network of IL-17 and IL-22 in coordination with these inflammatory cytokines is associated with the pathogenesis of GBS.…”
Section: Discussionmentioning
confidence: 99%
“…The latter then bind the corepressor molecule NCoR to exert antiinflammatory activity [37]. It is well established that inflammatory cytokines play an important role in the development of EAN as well as GBS [38]. CD4+ Th1 cells are involved in the pathogenesis of EAN by releasing inflammatory cytokines such as TNF-α and INF-γ.…”
Section: Ean Is a Canonical Animal Model To Study Gbs And Useful In Imentioning
confidence: 99%